Оптико-електронний мультиспектральний пристрій для визначення стану периферичного кровообігу - Павлов, С. В.; Козловська, Т. І.; Думенко, В. П.; Сидорук, О. О. (Vinnytsia National Technical University, 2016)
A brief overview of the photoplethysmographic method was given. The structural features of the skin and the principles of penetration of optical radiation into biological tissue depending on the wavelength were studied. Besides, the optimal wavelengths were determined to study the different layers of the skin. On the base of researches multispectral optoelectronic device to determine the state of the peripheral circulation was constructed.